Urgensi pendidikan karakter dalam menumbuhkan identitas nasional pada generasi-z - Ardana, Farizal Shafa (Maliki Interdisciplinary Journal, 2025)
In today's fast-paced digital era, Generation Z is growing up surrounded by global influences that often overshadow their sense of national identity. Constant exposure to foreign cultures and trends through social media and technology has made them more connected globally, but sometimes less grounded in the values of their own nation. This article explores the vital role of character education in helping young people reconnect with their national identity. Using a qualitative approach through literature review, the study highlights how integrating values such as mutual respect, cooperation, and love for the country into formal education can shape a stronger national consciousness among youth. The findings emphasize the importance of collaboration between schools, families, and communities in creating an environment where national values are consistently modeled and practiced. Properly implemented, character education has the potential to build a generation that is not only intellectually capable, but also proud of their cultural roots and committed to the future of their nation.